Disentangling Promotive and Buffering Protection: Exploring the Interface Between Risk and Protective Factors in Recidivism of Adult Convicted Males - Guay, Jean-Pierre (Criminal justice and behavior, 2020)
The quality of risk assessment instruments has improved greatly during the last 40 years. While assessing protective factors has become common practice, with some instruments now devoted entirely to such assessments, little is known about the effect of risk and protective factors on recidivism. The present study investigates the effects (promotive or buffering protective) of protective factors captured by the LS/CMI for a sample of 18,031 convicted adult males under the supervision of provincial services in Canada. Effects of protective factors and possible interactions between risk and protective factors were investigated using moderation analyses. Results indicate that protective factors can be both promotive and buffering protective for risk and that the benefits of protective factors are related to the risk to which people are exposed. Patterns of protective effects appear to differ for general and violent recidivism. Theoretical and clinical implications are discussed.